Assessment of malnutrition in cancer patients: a geriatric approach with the mini nutritional assessment - Ozlem Dogan; Hayriye Sahinli; Dogan Yazilitas (Frontiers in Nutrition)
Background and objectivesMalnutrition is a common problem among cancer patients, significantly impacting clinical outcomes and quality of life. This study aimed to evaluate the prevalence of malnutrition and its associated factors in geriatric cancer patients undergoing chemotherapy.Materials and methodsThis prospective study included 471 patients aged 65 years and older, conducted at Ankara Etlik City Hospital between January and December 2023. Patients’ demographic, clinical, and nutritional statuses were assessed using the Mini Nutritional Assessment (MNA). Nutritional status was classified as normal (MNA ≥ 24), at risk of malnutrition (MNA 17–23.5), and malnourished (MNA < 17). Depression and insomnia were evaluated using the Geriatric Depression Scale (GDS) and the Insomnia Severity Index (ISI), respectively. Factors associated with malnutrition were analyzed statistically.ResultsMalnutrition was identified in 20.5% of the patients. Malnutrition was significantly associated with radiotherapy (p = 0.001), surgical history (p = 0.001), adjuvant therapy (p = 0.002), metastatic disease (p = 0.011), low BMI (p < 0.001), high depression scores (p < 0.001), moderate-to-severe insomnia (p < 0.001), and the presence of comorbidities (p = 0.022). However, no significant association was found between pain and malnutrition (p = 0.07).ConclusionThis study highlights the multifactorial nature of malnutrition in geriatric cancer patients and emphasizes the importance of regular nutritional assessments using validated tools like MNA. Early detection and intervention can improve clinical outcomes and quality of life. However, the study has certain limitations, including being single-center, the use of self-reported measures, and the exclusion of palliative patients, which may affect the generalizability of the results.